Pendampingan Pembuatan Pupuk Kompos Menggunakan Drum Komposter pada Kelompok Warga Perumahan ATR 2 Jember: Pengabdian - Datik Lestari; Mira Andriani; Theo Mahiseta Syahniar; Putri Rahayu Ratri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The management of household organic waste is a growing challenge in residential areas due to increasing waste volumes and limited source-level treatment systems. This community service program aimed to build the capacity of residents in ATR-2 Housing, Jember, to process organic waste through assisted compost production using an aerobic drum composter. Activities included socialization, hands-on practice in filling and operating the drum composter, and monitoring and evaluation of the composting process. A 60-liter drum composter was operated using a layering technique of organic materials, addition of dry materials, and application of the EM4 activator. Results showed that liquid organic fertilizer could be harvested approximately one week after initial filling, while solid compost reached maturity within 30–40 days, characterized by a darker color, crumbly texture, and absence of foul odor. The program contributed to a reduction in organic waste volume, improved residents’ awareness and skills, and supported the use of compost on communal public facility planting areas. The mentoring-based approach proved effective and has potential for replication in other neighborhood or residential community settings.